2001
DOI: 10.7748/ns2001.05.15.33.33.c3020
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in rural care. Part 2: assessing the wider issues

Abstract: Opportunities now exist for nurses to use teleconsultation for the benefit of their patients. A systematic development of this type of nursing role through integration with broader service development would be valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…tele/videoconferencing) and use of Internet under the umbrella heading of eHealth. Alternative forms of service provision described in the literature include those employed in New Mexico (Shoup 1995), community health trusts in NZ (Barnett & Barnett 2001) and community nurse–prescribers in rural Scotland (MacDuff et al. 2001).…”
Section: Resultsmentioning
confidence: 99%
“…tele/videoconferencing) and use of Internet under the umbrella heading of eHealth. Alternative forms of service provision described in the literature include those employed in New Mexico (Shoup 1995), community health trusts in NZ (Barnett & Barnett 2001) and community nurse–prescribers in rural Scotland (MacDuff et al. 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The five most common themes were: Costs (in relation to provider and patient); Reductions in waiting time; Reduction in readmission rates; Patient/nurse satisfaction and benefits; Legal issues. Mennie concluded that there were substantial patient care benefits from nurse-led telemedicine, in terms of: Cost reductions (provider savings through telemedicine and patient savings on travel costs); Reduced waiting times; Reduced readmissions; High levels of patient satisfaction. Also, the nurse was able to: Deal with more complex cases; Complete all of the patient's care; Establish and maintain a very positive role with the patient; Experience high morale and job satisfaction; Have opportunities for professional development. A qualitative evaluation of the service in Letham was conducted in 1999. 57 Although the doctors involved expressed some reservations about the limited video quality, all three user groups were positive about the service: Patients accepted telemedicine as being a good way to consult their GP. The survey showed that 92% were satisfied or fairly satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Generally outcome measures found in evaluations of teledermatology services can be divided into three categories: measures of user satisfaction [7][8][9][10][11][12], measures of medical outcome [7,9,[13][14][15][16][17][18] and financial measures [19][20][21]. Few papers looked specifically at the role of nurses in telemedicine [22][23][24][25][26].…”
Section: Teledermatologymentioning
confidence: 99%